The impact of recording on listening - Clarke, E (Cambridge University Press, 2007)
The development of recording is arguably the most significant change to have affected music in the twentieth century. Never before have people had access to so much music and in so many different ways and with so many different patterns of use. This paper examines some of the effects of recording on listening, starting with a brief outline of an ecological theory of listening and focusing on three specific characteristics of recordings: the interpenetration of music and the wider environment; recordings as medium and as object; and the relationship between social and solitary listening practices. Recording has attracted both utopian and dystopian commentaries on its effects on musical culture, and the paper concludes by considering both the opportunities and the drawbacks of recordings as a means of access to music.